ANALISIS DEL DESEMPEÑO DE UN PREAMPLIFICADOR IMPLEMENTADO PARA LA RESPUESTA DE UN SIPM EN EL MARCO DEL EXPERIMENTO DUNE (2024)
The objective of this research was to analyze the performance of a preamplifier implemented for the response of a SiPM within the framework of the DUNE experiment. For its execution, a quantitative, descriptive methodology was used under an experimental approach. For its development, four phases were carried out. The first consisted of the simulation of the circuit with the established parameters, the second phase covered the design of the PCB, the third phase was based on the prototyping of the circuit and the fourth phase the performance of functional tests. For which the THS4501 operational amplifier and a BFP22 transistor were used as elements, the results showed that the prototype obtained The prototype obtained in this project allowed the acquisition of a board with SMD assembly capable of receiving any type of response signal from a photomultiplier silicon with optimal sensitivity and resolution that allowed detecting small events such as photons and filtering the signal, thus eliminating oversampling of the SiPM and ripple and turbulence of the input signal. It is concluded that the prototyping obtained in this project allowed us to detect small events such as the photon and to filter the signal, thus eliminating the oversampling of the SiPM and the ripple and turbulence of the input signal. Keywords: SiMP, silicon photomultipliers, temperatures, amplifier and transistor.